Beta band oscillations in the motor thalamus are modulated by visuomotor coordination in essential tremor patients - Basha, Diellor; Kalia, Suneil K.; Hodaie, Mojgan; Lopez Rios, Adriana L.; Lozano, Andres M.; Hutchison, William D. (Frontiers in Human Neuroscience, 2023)
Introduction Beta oscillations in sensorimotor structures contribute to the planning, sequencing, and stopping of movements, functions that are typically associated with the role of the basal ganglia. The presence of beta oscillations (13–30 Hz) in the cerebellar zone of the thalamus (the ventral intermediate nucleus – Vim) indicates that this rhythm may also be involved in cerebellar functions such as motor learning and visuomotor adaptation. Methods To investigate the possible role of Vim beta oscillations in visuomotor coordination, we recorded local field potential (LFP) and multiunit activity from the Vim of essential tremor (ET) patients during neurosurgery for the implantation of deep brain stimulation (DBS) electrodes. Using a computer, patients performed a visuomotor adaptation task that required coordinating center-out movements with incongruent visual feedback imposed by inversion of the computer display. Results The results show that, in ET, Vim beta oscillations of the LFP were lower during the incongruent center-out task than during the congruent orientation. Vim firing rates increased significantly during periods of low beta power, particularly on approach to the peripheral target. In contrast, beta power in the subthalamic nucleus of Parkinson’s disease (PD) patients did not differ significantly between the incongruent and the congruent orientation of the center-out task. Discussion The findings support the hypothesis that beta oscillations of the Vim are modulated by novel visuomotor tasks. The inverse relationship between the power of Vim-LFP beta oscillations and Vim firing rates suggest that the suppression of beta oscillations may facilitate information throughput to the thalamocortical circuit by modulation of Vim firing rates.